Dopamine-Induced Dysconnectivity Between Salience Network and Auditory Cortex in Subjects With Psychotic-like Experiences: A Randomized Double-Blind Placebo-Controlled Study. (21st November 2019) - Rössler, Julian; Rössler, Wulf; Seifritz, Erich; Unterrassner, Lui; Wyss, Thomas; Haker, Helene; Wotruba, Diana
Abstract: Dopamine is involved in the pathophysiology of schizophrenia. Disrupted salience processing by the salience network (SN) may be a central link between dysregulated dopamine function and psychotic symptoms. However, dopaminergic influence on the SN and its presumed influence on psychotic and subpsychotic symptoms or psychotic-like experiences in healthy individuals remain unclear. Therefore, we investigated dopamine-induced changes in functional connectivity of the right anterior insula (rAI), a central SN hub, and their association with psychotic-like experiences. We enrolled 54 healthy, right-handed male subjects in a randomized, double-blind, cross-sectional placebo-controlled experiment. Psychotic-like experiences were assessed using the revised Exceptional Experiences Questionnaire (PAGE-R). They then received either placebo ( n = 32) or 200 mg L-DOPA ( n = 33), a dopamine precursor, orally and underwent resting-state functional magnetic resonance imaging. In a seed-to-voxel approach, we analyzed dopamine-induced changes in functional connectivity of the rAI and assessed the relationship between functional connectivity changes and PAGE-R score. L-DOPA reduced functional connectivity between the rAI and the left auditory cortex planum polare. In the placebo group, we found a strong negative correlation between PAGE-R score and rAI to planum polare functional connectivity; in the L-DOPA group, there was a strong positive correlation between PAGE-R score and functional connectivity between rAI and planum polare. The PAGE-R score explained about 30% of the functional connectivity variation between rAI and planum polare in the two groups. Our findings suggest that psychotic-like experiences are associated with dopamine-induced disruption of auditory input to the SN, which may lead to aberrant attribution of salience.